Method for testing film expansion performance of Uv viscosity-reducing film
Through the systematic testing method, the dimensional changes, severity changes and elastic recovery data of UV mucosa during the film expansion process are monitored and recorded in real time, which solves the problem of ignoring viscosity and elastic recovery in the prior art, and realizes a multi-dimensional evaluation of the performance of UV mucosa membrane expansion.
Patent Information
- Application Number
- CN202411866040.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has shortcomings in evaluating the viscosity changes and elastic recovery performance of UV mucosa during the film expansion process. Traditional methods mainly focus on the size changes of the membrane and ignore the importance of viscosity and elastic recovery.
A systematic and comprehensive testing method is adopted, including steps S1 to S5, through a laser displacement sensor and a tensile tester, the dimensional change, viscosity change and elastic recovery data of the experimental film during the film expansion process is monitored and recorded in real time, and the corresponding change rate is calculated.
The ability to comprehensively evaluate the membrane expansion performance of UV mucosa from multiple dimensions provides more accurate and reliable data to help determine the membrane's scalability, adhesion and elastic recovery capabilities.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of UV anti-viscosity film performance testing, and in particular to a method for testing the film expansion performance of a UV anti-viscosity film. Background Art
[0002] UV anti-viscosity film is widely used in many fields such as semiconductor manufacturing, electronic component packaging, etc. In these application scenarios, film expansion operation is often a necessary process, and film expansion performance directly affects product quality and production efficiency.
[0003] However, in the existing technology, traditional methods often only focus on the dimensional changes of the film during the stretching process, while ignoring the changes in other important properties. During the film expansion process, the viscosity change of the UV anti-viscosity film is also a key factor. After film expansion, the viscosity of the film may decrease, thus affecting its adhesion effect on the adherend. Moreover, the elastic recovery performance of the UV anti-viscosity film is also very important. Some films may not be able to recover to their original state well after film expansion. Traditional testing methods rarely involve the evaluation of these characteristic changes. Summary of the invention
[0004] In view of the shortcomings of the prior art, the technical solution adopted by the present invention to solve the technical problems is: a method for testing the film expansion performance of a Uv anti-viscosity film, comprising the following steps: Step S1: prepare a circular UV anti-viscosity film sample as an experimental film, fix the experimental film on a film expansion device, mark 8 measuring points on the experimental film, and use a laser displacement sensor to record the initial coordinate positions of the measuring points; Step S2: starting the film expansion device to stretch the experimental film. During the stretching process, the position change of each measuring point is monitored in real time by using a laser displacement sensor to obtain dimensional change data and calculate the dimensional change rate; Step S3: Press the test plate on the center area of the test film, then use a tensile testing machine to pull up the test plate, record the tensile force value at the moment of pulling up, repeat the operation twice, obtain the tensile force change data and calculate the dimensional change rate; Step S4: releasing the tensile force of the film expansion device on the experimental film, measuring the position of the marked point on the experimental film with a laser displacement sensor, obtaining elastic recovery data and calculating the elastic change rate; Step S5: Record the size change rate, dimension change rate and elastic change rate during the film expansion process, and compare them with the standard change rate to complete the test of the film expansion performance of the UV anti-viscosity film.
[0005] A systematic and comprehensive test method framework for the film expansion performance of UV anti-viscosity films is provided, covering the complete process from sample preparation, tensile testing, viscosity testing to elastic recovery testing and final data comparison and evaluation, which can evaluate the film expansion performance of UV anti-viscosity films in multiple dimensions.
[0006] The present invention is further configured as follows: the diameter of the test film in step S1 is 100 mm, the stretching speed of the film expansion device in step S2 is 50 mm / min, and the stretching height is 30 mm. The diameter of the experimental film and the key parameters of the film expansion device are clarified, and the appropriate experimental film diameter can not only ensure the representativeness of the test, but also facilitate operation and data collection, provide specific quantitative standards for the experimental settings in the test process, reduce the deviation of the test results caused by the difference in the experimental film size and film expansion parameters, and improve the accuracy and repeatability of the test.
[0007] The present invention is further configured as follows: during the stretching process of step S2, the position change data of the data measurement point is recorded every 10 seconds, and the formula for calculating the size change rate is: d=d2-d1 / d1×100%, wherein d is the size change rate, d1 is the initial diameter of the experimental film, and d2 is the diameter of the experimental film after being stretched to the stretching height. The data recording frequency during the stretching process and the calculation formula for the size change rate are specified. A reasonable recording frequency can effectively capture the size change trend of the experimental film during the stretching process without generating too much redundant data; an accurate size change rate calculation formula can intuitively reflect the degree of size expansion of the experimental film during the film expansion process.
[0008] The present invention is further configured as follows: the specific steps of obtaining the viscosity change data in step S3 are: Step a1: Press the test plate on the central area of the test film, use a tensile testing machine to slowly pull up the test plate in a direction perpendicular to the film surface, and record the tensile force value at the moment of the first pulling; Step a2: Press the test plate against the center area of the test film with the same pressure again, then use the tensile testing machine to pull up the test plate again, and record the instantaneous tensile force value for the second time; The present invention is further configured as follows: the material of the test plate is a glass sheet, the surface flatness tolerance range is ±0.01mm, the pressure of the test plate pressing on the test film is 0.5MPa, the pressing time is 60s, and the tensile speed of the tensile tester is 1mm / min. The specific operation steps for obtaining viscosity change data are described, including two different stages of pressing and pulling up the test plate. This step-by-step testing method can effectively compare the changes in the viscosity of the experimental film before and after film expansion, eliminate the interference of other factors on the viscosity test results, and more accurately reflect the influence of the film expansion process on the viscosity of the UV anti-viscosity film.
[0009] The present invention is further configured as follows: the viscosity change rate formula is: F=(F1-F2) / F1×100%, wherein F is the elastic change rate, F1 is the tension value at the moment of the first pull-up, and F2 is the tension value at the moment of the second pull-up. The formula is simple and clear and based on the two tension test values, it can directly reflect the relative change degree of the viscosity of the experimental film before and after the film expansion, and expresses the viscosity change rate in the form of a percentage, which is convenient for intuitively understanding and comparing the viscosity changes of different experimental films or under different film expansion conditions.
[0010] The present invention is further configured as follows: the specific steps of obtaining the elastic recovery data in step S4 are: Step b1: releasing the tensile force on the test film, and starting the laser displacement sensor to monitor the position of the marking point on the test film; Step b2: Using a laser displacement sensor to measure the position of each marking point every 30 seconds, and calculating the restored displacement data of each marking point based on the measurement; The present invention is further configured as follows: the speed of the process of releasing the tensile force in step b1 is 10 mm / min, and the measurement time in step b2 is 0.1 s. The specific steps of obtaining elastic recovery data are described, including monitoring start after releasing the tensile force and regular position measurement. This method combining real-time monitoring and timed measurement can comprehensively record the recovery process of the experimental film after the tensile force is released, and capture the dynamic characteristics of its elastic recovery.
[0011] The present invention is further configured as follows: the formula for calculating the elastic change rate is: D=(D3-D2) / (D3-D1)×100%, wherein D is the elastic change rate, D1 is the initial diameter of the test membrane, D2 is the diameter of the test membrane after recovery, and D3 is the diameter of the test membrane after expansion.
[0012] The beneficial effects of the present invention are as follows: 1. The present invention can comprehensively evaluate the film expansion performance of the UV anti-viscosity film from multiple dimensions by measuring and calculating the dimensional change rate, viscosity change rate and elasticity change rate. The dimensional change rate reflects the degree of stretching and deformation of the film during the film expansion process, which helps to determine its scalability in different application scenarios; the viscosity change rate intuitively presents the effect of the film expansion operation on the film adhesion, which is crucial for applications involving pasting and fixing functions, such as in the semiconductor chip bonding process, to ensure that the appropriate adhesion can be maintained after film expansion to ensure the reliability of chip fixation; the elasticity change rate reveals the ability of the film to return to its original state after film expansion, which is of great significance for multiple cycles or the need to maintain shape stability, and can effectively predict its performance during long-term use.
[0013] 2. The present invention establishes a complete and standardized test process by specifying in detail each step from sample preparation to film expansion operation, viscosity test and elastic recovery test. This enables different laboratories or operators to follow unified specifications when conducting UV anti-viscosity film expansion performance tests, greatly reducing the result deviation caused by differences in test methods, which is beneficial to technical exchanges and data comparisons within the industry, and promotes the standardization process of the entire UV anti-viscosity film testing technology. DETAILED DESCRIPTION
[0014] The present invention is further described in detail below in conjunction with specific embodiments. The embodiments of the present invention are provided for the purpose of illustration and description, and are not intended to be exhaustive or to limit the present invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described to better illustrate the principles and practical applications of the present invention, and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses. Example
[0015] Prepare a circular UV anti-viscosity film test film with a diameter of 100mm, adjust the stretching speed of the film expansion device to 50mm / min, the stretching height to 30mm, a high-precision laser displacement sensor, a glass test plate with surface flatness that meets the requirements, and a tensile testing machine with a stretching speed of 1mm / min.
[0016] Experimental Group 1: Step S1: Fix the circular experimental film on the platform of the film expansion device, evenly mark 8 measurement points on the experimental film, and use a laser displacement sensor to record the initial coordinate positions of these measurement points. The coordinate recording accuracy reaches below the millimeter level to obtain the most accurate initial data.
[0017] Step S2: Start the film expansion device and start stretching the experimental film. During the stretching process, the laser displacement sensor continuously monitors the position changes of each measuring point at intervals of 10 seconds. When the stretching reaches the set height of 30 mm, the stretching is stopped and maintained for a period of time for subsequent measurement and calculation. According to the recorded initial diameter d1 and the diameter d2 after stretching to the height, the dimensional change rate is calculated using the formula d=(d2 - d1) / d1×100%. Set the initial diameter d1 to 100 mm and the diameter d2 after stretching to 130 mm, then the dimensional change rate d=(130-100) / 100×100%=30%.
[0018] Step S3: Place the glass test plate in the center area of the experimental film, use a pressure-applying device to press the test plate on the experimental film at a pressure of 0.5 MPa, keep pressing for 60 seconds, then use a tensile testing machine to slowly pull up the test plate in a direction perpendicular to the film surface, and record the tensile force value F1 at the moment of the first pull-up, assuming that F1 is 40 N. Next, press the test plate again in the center area of the experimental film with the same pressure, repeat the above tensile test operation, record the tensile force value F2 at the moment of the second pull-up, assuming that F2 is 30 N, and calculate the viscosity change rate F = (40 -30) / 40×100%=25% according to the viscosity change rate formula F=(F1- F2) / F1×100%.
[0019] Step S4: After the tensile test is completed, the tensile force of the film expansion device on the experimental film is slowly released at a speed of 10mm / min, and the laser displacement sensor is started at the moment of releasing the tensile force to monitor the position of the marking point on the experimental film. Subsequently, the laser displacement sensor is used to measure the position of each marking point every 30s, and the measurement time is 0.1s. The recovery displacement data of each marking point is calculated based on the measurement data. If the diameter of a marking point after film expansion is 130mm, the diameter after recovery is 110mm, and the initial diameter is 100mm, then according to the elastic change rate formula D=(D3-D2) / (D3-D1)×100%, the elastic change rate D = (130-110) / (130-100)×100%=66.7% is calculated.
[0020] Step S5: Compare the calculated dimensional change rate (30%), viscosity change rate (25%) and elasticity change rate (66.7%) with the preset standard change rate, assuming that the standard dimensional change rate is required to be no more than 40%, the standard viscosity change rate is required to be no more than 30%, and the standard elasticity change rate is required to be no less than 60%. By comparison, it can be seen that the dimensional change rate and viscosity change rate of the experimental film are within the standard range, and the elasticity change rate is slightly higher than the standard requirement, indicating that the UV viscosity reduction film performs well in film expansion performance, but the elastic recovery performance has room for improvement.
[0021] Experimental Group 2: Step S1: Fix the experimental film and mark 8 measurement points, and record the initial coordinate positions.
[0022] Step S2: Start the film expansion device to stretch the test film. During the stretching process, the laser displacement sensor monitors the position change of each measuring point and records the data. Assuming that the diameter d2 of the test film becomes 150mm after stretching, the dimensional change rate is calculated according to the formula d=(150-100) / 100×100%=50%.
[0023] Step S3: Conduct a viscosity test, the instantaneous pulling force F1 of the test plate when it is pulled up for the first time is 35 N, and the second time is 20 N. Calculate the viscosity change rate F=(35-20) / 35×100%=42.9%.
[0024] Step S4: Release the stretching force at a speed of 10 mm / min, and use a laser displacement sensor to monitor the position change of the marking point. Assuming that the diameter D3 of a certain marking point after film expansion is 150 mm, and the diameter D2 after recovery is 120 mm, the elastic change rate D = (150-120) / (150-100) × 100% = 60%.
[0025] Step S5: Compare the standard change rate. If the standard size change rate is not more than 40%, the standard viscosity change rate is not more than 30%, and the standard elasticity change rate is not less than 60%, it can be seen that the size change rate of the experimental film exceeds the standard, the viscosity change rate also exceeds the standard, and the elasticity change rate just reaches the standard. This shows that the UV viscosity reduction film has poor film expansion performance, and has deficiencies in dimensional stability and viscosity retention. It is necessary to further improve the material formula or production process to meet application requirements.
[0026] Through these two experimental groups, we can clearly see how the patented test method of this invention is applied to the actual UV anti-viscosity film expansion performance test, and evaluate and judge the material performance based on the test results, providing a strong basis for the research and development, production and application of the material. Refer to the table below.
[0027] Control group: Step 1: Fix one end of the UV anti-viscosity film sample on the stretching fixture and the other end on the movable clamp. Manually rotate the screw to start stretching, and stop stretching when the film is obviously deformed; Step 2: Use a vernier caliper to measure the length and width of the film before and after stretching; Step 3: Press the test plate on the center area of the unstretched UV anti-viscosity film sample, apply a certain pressure by hand, and then use a spring scale to pull up the test plate at an angle of about 30-60 degrees, record the maximum reading of the spring scale as the adhesion value, repeat the above operation again, and get the second adhesion value to calculate the so-called "viscosity change rate".
[0028] Step 4: After the tensile test is completed, directly release the tensile clamp and let the membrane recover naturally. After 5-10 minutes, measure the size of the membrane again with a vernier caliper, observe its recovery, and calculate the elastic recovery rate.
[0029] By comparing with the invention patent test method of the experimental group, it can be seen that the traditional test method has obvious deficiencies in the standardization of experimental materials, the accuracy of test equipment, the standardization of test process and the accuracy of data calculation. This also highlights the advantages and advancement of the patented test method of the present invention, which can more accurately and comprehensively evaluate the film expansion performance of UV anti-viscosity film.
[0030] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention are implemented according to the conventional means in the field unless otherwise specified and limited.
Claims
1. A method for testing the film expansion performance of a Uv anti-viscosity film, characterized in that: The following steps are involved: Step S1: prepare a circular UV anti-viscosity film sample as an experimental film, fix the experimental film on a film expansion device, mark 8 measuring points on the experimental film, and use a laser displacement sensor to record the initial coordinate positions of the measuring points; Step S2: starting the film expansion device to stretch the experimental film. During the stretching process, the position change of each measuring point is monitored in real time by using a laser displacement sensor to obtain dimensional change data and calculate the dimensional change rate; Step S3: Press the test plate on the center area of the test film, then use a tensile testing machine to pull up the test plate, record the tensile force value at the moment of pulling up, repeat the operation twice, obtain the tensile force change data and calculate the dimensional change rate; Step S4: releasing the tensile force of the film expansion device on the experimental film, measuring the position of the marked point on the experimental film with a laser displacement sensor, obtaining elastic recovery data and calculating the elastic change rate; Step S5: Record the size change rate, dimension change rate and elastic change rate during the film expansion process, and compare them with the standard change rate to complete the test of the film expansion performance of the UV anti-viscosity film.
2. The method for testing the film expansion performance of a UV anti-viscosity film according to claim 1, characterized in that: The diameter of the test film in step S1 is 100 mm, the stretching speed of the film expansion device in step S2 is 50 mm / min, and the stretching height is 30 mm.
3. The method for testing the film expansion performance of a UV anti-viscosity film according to claim 1, characterized in that: During the stretching process in step S2, the position change data of the data measurement point is recorded every 10 seconds, and the formula for calculating the dimensional change rate is: d=d2-d1 / d1×100%, wherein d is the dimensional change rate, d1 is the initial diameter of the experimental film, and d2 is the diameter of the experimental film after being stretched to the stretching height.
4. The method for testing the film expansion performance of a UV anti-viscosity film according to claim 1, characterized in that: The specific steps of obtaining the viscosity change data in step S3 are: Step a1: Press the test plate on the central area of the test film, use a tensile testing machine to slowly pull up the test plate in a direction perpendicular to the film surface, and record the tensile force value at the moment of the first pulling; Step a2: Press the test plate against the center area of the test film with the same pressure again, then use the tensile testing machine to pull up the test plate again, and record the instantaneous tensile force value for the second time.
5. The method for testing the film expansion performance of a UV anti-viscosity film according to claim 4, characterized in that: The material of the test plate is a glass sheet, and the surface flatness tolerance range is ±0.01 mm. The pressure of the test plate pressing on the test film is 0.5 MPa, the pressing time is 60 s, and the tensile speed of the tensile testing machine is 1 mm / min.
6. The method for testing the film expansion performance of a UV anti-viscosity film according to claim 4, characterized in that: The viscosity change rate formula is: F=(F1-F2) / F1×100%, where F is the elastic change rate, F1 is the tension value at the moment of the first pull, and F2 is the tension value at the moment of the second pull.
7. The method for testing the film expansion performance of a UV anti-viscosity film according to claim 1, characterized in that: The specific steps of obtaining elastic recovery data in step S4 are: Step b1: releasing the tensile force on the test film, and starting the laser displacement sensor to monitor the position of the marking point on the test film; Step b2: Use a laser displacement sensor to measure the position of each marking point every 30 seconds, and calculate the restored displacement data of each marking point based on the measurement.
8. The method for testing the film expansion performance of a UV anti-viscosity film according to claim 7, characterized in that: The speed of releasing the tensile force in step b1 is 10 mm / min, and the measuring time in step b2 is 0.1 s.
9. The method for testing the film expansion performance of a UV anti-viscosity film according to claim 7, characterized in that: The formula for calculating the elastic change rate is: D=(D3-D2) / (D3-D1)×100%, where D is the elastic change rate, D1 is the initial diameter of the test membrane, D2 is the diameter of the test membrane after recovery, and D3 is the diameter of the test membrane after expansion.